The tentative application of en bloc concept in the pediatric brain tumor: Experience from a large pediatric center in china - Cao, Liangliang; Tian, Shuaiwei; Ma, Wenkun; Ni, Zhouwen; Tian, Gang; Zhao, Yang; Wang, Qinhua; Xu, Zhen; Wang, Jiajia; Liang, Zhuangzhuang; Zhao, Heng; Yang, Lingrui; et al. (Frontiers in Oncology, 2022)
Background: Children are more susceptible to the higher rate of massive blood transfusion because of the less allowable blood loss and lower intraoperative tolerance to blood loss during the resection of brain tumors. The surgical concept of en bloc resection, which is widely used in other tumors, may contribute to the improvement of brain tumor resection. However, the comprehensive study of it in pediatric brain tumors is deficient. Objective: To investigate the short-term outcome of en bloc concept and factors associated with the application of en bloc concept in pediatric brain tumors. Methods: According to the surgical concept involved, the patients were divided into three subgroups-complete en bloc concept, partial en bloc concept and piecemeal concept. The matching-comparison (complete and partial en bloc concept groups VS piecemeal concept group) was conducted to investigate the effect of the en bloc concept on the short-term outcomes. Then the patient data from January 2018, when the en bloc concept was routinely integrated into the brain tumor surgery in our medical center, was reviewed and analyzed to find out the predictors associated with the application of en bloc concept. Results: In the en bloc group, the perioperative parameters, including hospital stay(p=0.001), PICU stay(p=0.003), total blood loss(p=0.015), transfusion rate(p=0.005) and complication rate(p=0.039), were all significantly improved. The multinomial logistic regression analysis showed that tumor volume, bottom vessel and imaging features, such as, encasing nerve or pass-by vessel, finger-like attachment, ratio of “limited line” and ratio of “clear line”, were independent predictors for the application of en bloc concept in our medical center. Conclusion: This study supports the application of complete and partial en bloc concept in the pediatric brain tumor surgery based on the preoperative evaluation of imaging features, and compared with piecemeal concept, en bloc concept can improve the short outcomes without significant increases in the neurological complication. Large series and additional supportive evidence are still warranted.